Hydrolysis-Based Hydrogen Generation Investigation of Aluminum System Adding Low-Melting Metals - Zeng Gao; Fei Ji; Dongfeng Cheng; Congxin Yin; Jitai Niu; Josip Brnic (Energies, 2021)
In this age of human civilization, there is a need for more efficient, cleaner, and renewable energy as opposed to that provided by nonrenewable sources such as coal and oil. In this sense, hydrogen energy has been proven to be a better choice. In this paper, a portable graphite crucible metal smelting furnace was used to prepare ten multi-element aluminum alloy ingots with different components. The microstructure and phase composition of the ingots and reaction products were analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM), and differential scanning calorimetry (DSC). The reaction was carried out in a constant temperature water bath furnace at 60 °C, and the hydrogen production performance of the multi-element aluminum alloys in different proportions was compared by the drainage gas collection method. The experimental results show that the as-cast microstructure of Al–Ga–In–Sn aluminum alloy is composed of a solid solution of Al and part of Ga, and a second phase of In3Sn. After the hydrolysis reaction, the products were dried at 150 °C and then analyzed by XRD. The products were mainly composed of AlOOH and In3Sn. Alloys with different compositions react at the same hydrolysis temperature, and the hydrogen production performance is related to the ratio of low-melting-point metal elements. By comparing two different ratios of Ga–In–Sn (GIS), the hydrogen production capacity and production rate when the ratio is 6:3:1 are generally higher than those when the ratio is 7:2:1. The second phase content affects the hydrogen production performance.